Spatial Structure Analysis in Regional Development Context at Samosir Regency - Permana, Sendi; Siburian, Pukarda Jordan; Lubis, Darwin Parlaungan; Damanik, M Ridha Syafii; Rahmadi, M Taufik; Ryabtsev, Vladimir (Tunas Geografi, 2023)
Regional inequality or disparity is a natural consequence of development and an unavoidable stage. This happens because of differences in population, natural resource potential and geographical conditions in each region. This research aims to analyze public service centers, inter-district interactions, and settlement patterns in the context of regional development in Samosir Regency. The study uses a descriptive method with a quantitative approach to analyze the centers of public services, inter-district interactions, and settlement patterns among districts in Samosir Regency using the tools of centrality index analysis, gravity model, and nearest neighbor analysis. The analysis results show that the public service facilities in Samosir Regency in 2021 include 517 units of educational facilities, 442 units of healthcare facilities, 561 units of religious facilities, and 2,418 units of economic facilities, with the service center located in Pangururan District with a total availability of 1,081 units, which has the highest centrality value of 966.63. The largest inter-district interactions occur in Palipi District with a total interaction of 11,671,532.31, while the smallest interaction occurs in Simanindo District with a total interaction of 749,250.15. The settlement pattern in Samosir Regency consists of 1 district with a random settlement pattern and 8 other districts with clustered settlement patterns. In the development of Samosir Regency, the influence of district interactions, service centers, and settlement patterns are important factors to be considered.Keywords: District, Service Center, Interaction, Settlement Pattern